Women’s Empowerment Through Home-Based Gold Thread Embroidery in Naras Village, Pariaman City: A Case Study of Indah Mayang Embroidery - Festy Azkia Fais; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study examines the empowerment of women through home-based gold embroidery handicraft activities in Naras Village, Pariaman City, focusing on the Sulaman Indah Mayang Group. The study is based on the important role of women as agents of social change and contributors to family welfare through productive economic activities. It aims to describe the forms and processes of empowerment, analyze strategies for skill development, business management and marketing, identify challenges faced by women artisans, and examine the role of home-based enterprises in supporting women with dual roles as housewives and income earners. This research used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. Informants were selected using purposive and snowball sampling techniques. Data were analyzed through reduction, presentation, and conclusion drawing, while validity was ensured through triangulation. The findings show that empowerment was carried out through skill improvement, social capacity building, and better business management. Strategies included continuous training, financial recording, and marketing through conventional and digital media. Main challenges were limited capital, weak modern marketing skills, and low youth interest in continuing the craft. Home-based enterprises provide flexibility for women to manage domestic duties while earning income, improving their economic independence and preserving Minangkabau cultural heritage.. Keywords: Women Empowerment, Home-Based Industry, Gold Embroidery, Cultural Heritage, Non-Formal Education, Pariaman City